SWINDU (Smart Farming dengan Wind Turbine) = Rancang Bangun Wind Turbine Sederhana berbasis ESP32 untuk Smart Farming Deteksi Kelembapan Tanah pada Sayuran Pokcoy - Abdulah, Muhammad Zaki; Rahmadani, Annisa; Anyeler, Desvita Elvira; Setyaji, Galih; Gunawan, Maulana Fadhilah (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2024)
This research describes the design and implementation of a wind turbine system integrated with an ESP32 microcontroller to detect soil moisture in pakcoy vegetable plants. The main objective of this research is to create a sustainable solution that combines renewable energy with smart crop monitoring technology. The system uses a wind turbine as the main energy source that can generate electricity to operate the soil moisture sensor and DHT11 temperature sensor. The data obtained from these two sensors is used to measure and monitor the environmental conditions of pakcoy plants in real-time. The goal is to support the development of renewable energy, such as wind turbines, to address climate change and safeguard natural resources. Benefits include a reduction in the negative impacts of conventional energy and support for global efforts to address climate change. The methodology involves designing a wind turbine prototype, using temperature and humidity sensors, and integrating smart farming systems. The research also includes a research schedule. The results are expected to be an efficient prototype for generating electrical energy and a MitApp application for monitoring crop and wind energy data. This proposal is relevant to environmental and climate change issues and has the potential for a positive impact on sustainability and the environment.